1985
DOI: 10.1159/000124083
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Autoradiographic and Immunocytochemical Study of <sup>3</sup>H-Corticosterone Target Neurons and Catecholamine Neurons in Rat and Mouse Lower Brain Stem

Abstract: Target neurons for 3H-corticosterone were identified by autoradiography and tyrosine hydroxylase containing neurons were identified by immunocytochemistry in the same sections of lower brain stem of 38-day-old rats, 10-day-old rats and adult mice. In all animals studied, the same topographic distribution of neurons was found which exibited a nuclear accumulation of 3H-corticosterone. Target neurons for 3H-corticosterone were widely distributed in the brain stem. Motor neurons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They should therefore represent an important site of action of glucocorticoid hormones secreted from the adrenal glands. A combined autoradiographic and immunocytochemical study (26) of [3H]corticosterone target neurons and catecholaminergic neurons did not show, but did not exclude, a direct genomic action of corticosterone on catecholaminergic neurons. Previous studies (4,5,8) have shown that the noradrenergic, adrenergic, and 5-hydroxytryptaminergic neurons respond to stress by changing their amine levels and utilization.…”
Section: Discussionmentioning
confidence: 77%
“…They should therefore represent an important site of action of glucocorticoid hormones secreted from the adrenal glands. A combined autoradiographic and immunocytochemical study (26) of [3H]corticosterone target neurons and catecholaminergic neurons did not show, but did not exclude, a direct genomic action of corticosterone on catecholaminergic neurons. Previous studies (4,5,8) have shown that the noradrenergic, adrenergic, and 5-hydroxytryptaminergic neurons respond to stress by changing their amine levels and utilization.…”
Section: Discussionmentioning
confidence: 77%
“…In vertebrate nervous systems, neural target cells for gonadal steroids, glucocorticoids, mineralocorticoids, and vitamin D3 have been identified (e.g., Pfaff, 1980;Stumpf, Sar, and Clark, 1982;Birmingham, Sar, and Stumpf, 1984;Duncan and Stumpf, 1985;Reul and DeKloet, 1986). A notable feature of steroid hormone receptor distribution in vertebrate nervous systems is that only anatomically restricted subsets of neurons bear receptors for these hormones.…”
Section: Developmental Patterns Of Ecdysteroid Binding In the Manducamentioning
confidence: 99%